Knowledge assessment of nurses working in an intensive care unit on hemodynamic monitoring (Revista Brasileira Multidisciplinar, 2021)
The nurse who works in the ICU must have technical-scientific knowledge about hemodynamic monitoring, as it is his responsibility to ensure that the monitored parameters are reliable, and based on these, critically assess the patient's condition. This study aimed to assess the knowledge of nurses working in the ICU on hemodynamic monitoring. This is a cross-sectional descriptive-exploratory study with a quantitative approach, carried out in a public hospital of high complexity located in the city of Caruaru / PE. It was found that nurses consider themselves able to perform any type of monitoring, being the non-invasive the most used. It was pointed out that its main use is for diagnostic, therapeutic and prognostic purposes and that monitoring needs to be added to the physical examination. It is concluded that the nurses' knowledge about hemodynamic monitoring in the ICU is satisfactory, with correct answers for most of the items evaluated regarding ability, usefulness and its association with physical examination.
Keywords: Nursing; Hemodynamic Monitoring; Knowledge; Intensive Therapy